2010
DOI: 10.1080/10615800802638279
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation strategies as mediators of the association between level of attachment security and PTSD symptoms following trauma in adulthood

Abstract: Although, a link between attachment and posttraumatic stress disorder (PTSD) symptoms has been established, the mechanisms involved in this link have not yet been identified. Furthermore, attachment has been systematically measured by self-report questionnaires, which are prone to perceptual bias. The first goal of this study was to examine the link between PTSD symptoms and attachment security level, as measured with a security index created from the Adult Attachment Projective interview. The second goal was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 51 publications
1
63
0
Order By: Relevance
“…Thus, one candidate variable that is likely to be associated with PTSD symptoms and academic burnout is parental attachment (Aspelmeier, Elliott, & Smith, 2007; Duchesne & Larose, 2007; Han, 2006). Lack of stress-reducing secure attachment often results in PTSD in adolescents (Benoit, Bouthillier, Moss, Rousseau, & Brunet, 2010; Dieperink, Leskela, Thuras, & Engdahl, 2001). Many researchers have theorized and investigated parental attachment as a resiliency factor for traumatized children and adolescents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one candidate variable that is likely to be associated with PTSD symptoms and academic burnout is parental attachment (Aspelmeier, Elliott, & Smith, 2007; Duchesne & Larose, 2007; Han, 2006). Lack of stress-reducing secure attachment often results in PTSD in adolescents (Benoit, Bouthillier, Moss, Rousseau, & Brunet, 2010; Dieperink, Leskela, Thuras, & Engdahl, 2001). Many researchers have theorized and investigated parental attachment as a resiliency factor for traumatized children and adolescents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence to support this hypothesis, showing that emotion regulation strategies mediate the association between secure attachment and lower levels of PTSD symptoms [38]. Research has consistently shown that secure attachment is negatively associated with the subsequent development of posttraumatic stress disorder (PTSD) in a variety of adult trauma victims [39].…”
Section: Predictors Of Ptsdmentioning
confidence: 89%
“…Another important area of research regarding trauma has highlighted the process of affect regulation (Benoit et al 2009). The study of affect regulation is not new; research in this area spans fields including psychology (Mikulincer et al 2003), neurobiology (Schore 1999), and marriage and family therapy (Kobak and Hazen 1991).…”
Section: Introductionmentioning
confidence: 99%